Supporting and promoting reflective thinking processes in an undergraduate Medical Imaging program - Maresse, Sharon; McKay, Jan; Grellier, Jane (Higher Education Research and Development Society of Australasia, Inc, 2012)
Notions of reflective practice are now well-accepted in many health professions. For those involved in professional, clinical practice education, reflective practice is becoming a central component. Much research is required as to how to help students develop their reflective writing processes, rather than just using writing as a tool to assess their understandings, or as a mechanistic process. In particular, there is little consideration in the literature of effective strategies for first-year student health professionals. The authors are involved in a Medical Imaging program at Curtin University, and participate in an ongoing research project designed to explore the curriculum development, teaching and assessment of students’ reflective writing. Medical Imaging students are introduced to reflective writing in their first semester of studies through a strategy that incorporates theoretical knowledge, writing practice and comprehensive feedback. Academic staff from the Medical Imaging discipline work in partnership with academic literacies staff to support students in developing their reflective processes. The strategy implemented for Curtin University Medical Imaging students during the first semester of first year has been found to support students to develop and progress their understanding and skills in reflective practice and reflective writing.